Aging workforce and firm growth in the context of "extreme" employment growth events - Antje Schimke (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2014)
In recent years demographic aging and its consequences have been recognized and discussed on macroeconomic levels, such as health care system, infrastructure, housing and labour market. However, the consequences are not only present on the macroeconomic level but also affect microeconomic issues such as a firm's growth and workforce. This exploratory study realises a microeconomic issue and investigates the linkage between aging workers and employment growth. More precisely, it aims to analyse the potential effect that age composition of a firm's workforce may have on a firm's employment growth. The study applies a linked employer-employee dataset of 2100 German firms, covering the time period from 2001 to 2006. We used quantile regression techniques to address the aging effect in the context of extreme employment growth events. The empirical investigation shows that, on average, employment growth slows down as the average age of the workforce increases.
urn:nbn:de:swb:90-378305
Keywords: J11; J21; L22; O40; 330; workers aging; workforce; 'extreme' employment growth events; demographic trends; age management